Intraperitoneal Hemorrhage in a Pregnant Woman with Hyperemesis Gravidarum: Vitamin K Deficiency as a Possible Cause - Yosuke Baba; Hiroyuki Morisawa; Koyomi Saito; Hironori Takahashi; Kazuma Rifu; Shigeki Matsubara (Case Reports in Obstetrics and Gynecology)
Hyperemesis gravidarum can cause various vitamin deficiencies. Vitamin K deficiency can lead to coagulopathy or hemorrhagic diathesis. A nulliparous Japanese woman with hyperemesis gravidarum at 105/7 weeks was admitted with giant myoma, intestinal obstruction, and abdominal pain. Treatment for a degenerative myoma was instituted with intravenous antibiotics. The abdominal pain ameliorated, but intestinal obstruction persisted. At 166/7 weeks, we performed laparotomy for release of intestinal obstruction, when intraabdominal bleeding of 110 mL existed. Blood tests revealed coagulopathy secondary to vitamin K deficiency. The coagulopathy responded to intravenous vitamin K injection. Coagulopathy due to vitamin K deficiency can occur with hyperemesis gravidarum, and coexisting intestinal obstruction and broad-spectrum antibiotics can aggravate the deficiency.